Voluntary folic acid fortification levels of food staples in Ireland continue to decline: further implications for passive folic acid intakes?. (28th October 2019) - Egan, Elizabeth; Kelly, Frances; Sweeney, Mary Rose
Abstract: Background: Ireland previously had widespread voluntary fortification but research at Dublin City University carried out in 2014 by our research group demonstrated a major decline in the number of food staples fortified with folic acid in Irish supermarkets over the previous 10 years. The aim of the study was to repeat the audit conducted 3 years ago to compare the levels of folic acid fortification of foodstuffs over this time-frame. Methods: Over a period of 8-weeks between June and August 2017, the nutrition labels of all foodstuffs that might typically be fortified with micronutrients for sale in the supermarkets with the majority of market share in Ireland were examined. The amount of added folic acid detailed on the label was compared with those captured in 2014. Results: In total, 1081 products with added micronutrients were examined. In percentage terms, there has been a decline of Folic Acid (FA) fortified products within the food groups—spreads, breads, cereals, cereal snacks, milks, fruit juices, yogurts/yogurt drinks and energy drinks since 2014. Discussion: The number of food staples fortified with FA continues to decline demonstrating that voluntary fortification in Ireland is no longer an effective measure for passively augmenting the folic acid levels of consumers.